Gene flow, biodiversity, and genetically modified crops: Weedy rice in Thailand - Schaal,B.A. (2015)
© Cambridge University Press 2010. The domestication of plants and animals and the development of agriculture some 10,000 years ago has led to profound changes in the environment and to biodiversity (Diamond 1997; Smith 1998). As natural communities were replaced by pastures and fields, native species were displaced or their habitats fragmented (Heywood 1995; Millennium Ecosystem Assessment 2005). The extirpation of native species began with the earliest agricultural communities in the Middle East and Asia and continues today. Every major advance in agriculture, from the development of new crops to mechanized farming, has environmental consequence. The most recent change in agricultural practice is the planting of genetically modified (GM) crops. First developed and legalized in the 1990s, today the majority of crops in the United States are GM, with approximately 90% of the U.S. soybean crop GM for herbicide tolerance (U.S. Department of Agriculture 2008). GM crops are varieties that have been transformed by using a biological or physical method to insert specific genes into a genome (Chrispeels&Sadava 2003). The inserted genes, transgenes, can come from another species or from the same species. In contrast, most varieties of nontransgenic crops are produced by traditional and modern methods of crop improvement and selective breeding (Chrispeels&Sadava 2003). Other descriptions for such GM crops are recombinant or genetically engineered crops. The specific methods of genetic manipulation used to produce a GM crop are not thought to have any serious consequences (National Research Council 2002), but rather the consideration of most concern is the specific nature of the introduced transgene. Because the method of crop improvement has little effect, some researchers have argued that the distinction between GM crops and non-GM crops is artificial; crops produced by traditional means of plant breeding are also GM (Federoff&Brown 2004). This point is important: The issues and concerns that have been raised about recently developed GM crops are also of concern regarding traditional crop varieties.